A integração das necessidades de usuários e projetistas como fonte de inovação para o projeto - Francisco Duarte; Carolina Conceição; Cláudia Cordeiro; Francisco Lima (Universidade do Porto, 2008)
The purpose of this work is to present and characterize the contribution of ergonomics to workplace design projects. Reflecting on the practice of a design project of an integrated control centre allowed us to highlight that the articulation and process of checking compatibility among the needs of different users and designers is at the origin of the innovations present in the implemented solutions. Ergonomic intervention in the workplace design shows that the architectural programme does not entirely define what is required by the users. This definition is progressive and enriched by ergonomic analysis of the work. In a similar way, the execution stage of a construction is a stage of re-conception as well as one of revising previous decisions. At this stage, the ergonomic intervention leads to new decisions, creating spheres of discussion among the different logics and foundations involved.